Light input pathways to the circadian clock of insects with an emphasis on the fruit fly Drosophila melanogaster - Helfrich-Förster, Charlotte (J Comp Physiol A Neuroethol Sens Neural Behav Physiol, 2019)
Light is the most important Zeitgeber for entraining animal activity rhythms to the 24-h day. In all animals, the eyes are the main visual organs that are not only responsible for motion and colour (image) vision, but also transfer light information to the circadian clock in the brain. The way in which light entrains the circadian clock appears, however, variable in different species. As do vertebrates, insects possess extraretinal photoreceptors in addition to their eyes (and ocelli) that are sometimes located close to (underneath) the eyes, but sometimes even in the central brain. These extraretinal photoreceptors contribute to entrainment of their circadian clocks to different degrees. The fruit fly Drosophila melanogaster is special, because it expresses the blue light-sensitive cryptochrome (CRY) directly in its circadian clock neurons, and CRY is usually regarded as the fly’s main circadian photoreceptor. Nevertheless, recent studies show that the retinal and extraretinal eyes transfer light information to almost every clock neuron and that the eyes are similarly important for entraining the fly’s activity rhythm as in other insects, or more generally spoken in other animals. Here, I compare the light input pathways between selected insect species with a focus on Drosophila’s special case.